QEEG analysis during bicycle riding for Parkinson's patient - Lattika Tiawongsuwan (2018)
© 2014 IEEE. Parkinson's disease is one of movement disorder that affected to quality of life. The exercise training can improve movement of patients. The aim of this study was to investigate the effect of bicycle riding to the brain activity by observing the absolute power and coherence revealed by the quantitative electroencephalogram (QEEG). The participants consisted of four healthy individuals. Each participant rode a stationary bicycle. The QEEGs of before biking, during biking and after biking were observed. The result showed that the brain activity of during biking will increase both absolute power and coherence when compared with before biking and after biking. Therefore, we suggest that cycling could maintain high coherence across the motor area which is potentially being a good exercise for Parkinson's patient.